2020
DOI: 10.1016/j.adro.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation of High-Grade Gliomas: A Retrospective Analysis of 198 Patients Based on the Charité Data Set

Abstract: Purpose There is no standard of care for recurrent high-grade glioma. Treatment strategies include reresection, reirradiation, systemic agents, intratumoral thermotherapy using magnetic iron-oxide nanoparticles (“nanotherapy”), and tumor treating fields. Only a small number of patients are eligible for reresection, and because many patients receive a full course of radiation therapy, there is fear of reirradiation-induced morbidity. Modern radiation techniques have resulted in greater acceptance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Concomitant and/or adjuvant treatment with temozolomide has resulted in longer overall survival and progression-free survival times compared with radiation alone, but this is generally limited to MGMT methylated tumors [ 13 , 48 , 63 , 72 ]; in addition, no clear survival advantages have been observed by other authors [ 58 , 74 , 85 ]. Some studies suggested significantly longer survival with the addition of bevacizumab to both SRS and fractionated SRT compared to reirradiation alone [ 38 , 50 , 52 , 76 , 78 ]; in contrast, other studies failed to demonstrate survival advantages [ 30 , 68 , 69 , 85 ]. Overall, the different prognostic impact of chemoradiation over radiation alone in patients with recurrent GBM remains to determined in prospective trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concomitant and/or adjuvant treatment with temozolomide has resulted in longer overall survival and progression-free survival times compared with radiation alone, but this is generally limited to MGMT methylated tumors [ 13 , 48 , 63 , 72 ]; in addition, no clear survival advantages have been observed by other authors [ 58 , 74 , 85 ]. Some studies suggested significantly longer survival with the addition of bevacizumab to both SRS and fractionated SRT compared to reirradiation alone [ 38 , 50 , 52 , 76 , 78 ]; in contrast, other studies failed to demonstrate survival advantages [ 30 , 68 , 69 , 85 ]. Overall, the different prognostic impact of chemoradiation over radiation alone in patients with recurrent GBM remains to determined in prospective trials.…”
Section: Resultsmentioning
confidence: 99%
“…Hypofractionated SRT with or without systemic therapy has been frequently used in the setting of recurrent GBM. Treatments include moderately (generally 2.5–3.5 Gy per fraction) and high-dose (5 Gy or more per fraction) hypofractionated schedules (Table 2 ) [ 12 , 13 , 55 69 ]. Because of its higher degree of precise patient positioning and accurate dose delivery, SRT has superseded conventional RT in clinical practice in the last two decades for the treatment of patients with recurrent tumors.…”
Section: Survival Outcomes and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Possible treatment strategies for recurrent malignant gliomas (rMGs) include second-line CMTs, surgery with or without adjuvant therapies, and RT ( 2 , 6 , 7 ). Reirradiation appears to be an efficacious and safe treatment modality, providing survival benefits with acceptable risk ( 8 , 9 ). Among different reirradiation modalities, hypofractionated stereotactic radiotherapy (HFSRT) has shown promising results as it allows delivery of a large total dose, in a precise target volume and short treatment duration ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%